Linguistic Discoveries: Tracing Grammatical Errors in the Translation of Qasas Al-Nabiyyīn by Abu Hasan Ali Hasani Nadwi - Satori, Achmad; Suparno, Darsita; Aqil Assyauqi, Wahyu; Wahidah, Wardah; Anas, Muhammad; Rokhim, Minatur; Zakaizak, Fathalla Muhamed Fathalla (Ta’lim al-’Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2023)
This article aims to understand the grammatical errors in the translated text of "QasasAl-Nabiyyīn" by Abu Hasan Ali Hasani Nadwi. This research uses the descriptivequalitative method to identify morphological and syntactic errors in the translated text.Data collection was done by collecting the original text of the source language and itstranslation in the book "Qasas Al-Nabiyyīn." The data collection steps involvedidentifying pairs of both languages for grammatical analysis, followed by data analysisto identify grammatical errors. The analysis results showed 18 grammatical errors in thetranslation of the book, consisting of 7 morphological errors and 11 syntactic errors.These errors impact the incompatibility of the message contained in the source text. Inorder to correct the grammatical errors, a correction analysis was conducted on thetarget language, especially in Indonesian, by referring to the applicable grammaticalrules. This article concludes that correcting grammatical errors can improve theaccuracy and clarity of the message in the translation of "Qasas Al- Nabiyyīn" so that itcan be more effectively conveyed to readers who speak the target language. Thisanalysis contributes to a practical understanding of the importance of paying attentionto grammatical aspects in translating religious texts. Recommendations for futureresearch include developing more effective translation strategies involving source andtarget language experts. Research can expand the scope of analysis to explore semanticand pragmatic aspects of translated texts.